Eksistensi Krumpyung Serambu: Studi Etnografi Musik Tradisional di Era Digitalisasi - Zakarias Aria Widyatama Putra (FKIP, Universitas Palangka Raya, 2024)
Krumpyung Serambu is an artisan, maker, and traditional music studio located in Tegiri Hamlet, Hargowilis Village, Kokap District, Kulon Progo Regency. In the era of digitalization, there are certainly many opinions and facts that reveal the anxiety for traditional music, including Krumpyung, to remain and develop. Ethnographic study as a method tries to reveal the existence of Krumpyung Serambu in the digitalization era. Using a realist ethnographic model, the answers in this paper refer to data from participant observation and in-depth interviews conducted with Serambu informants. Data processing and analysis are done by using Spradley's technique with the stages of domain analysis, taxonomy analysis, component analysis, and cultural theme analysis. As a result, the existence sub-domain that refers to human activities such as the recognition of Krumpyung Serambu, Krumpyung Serambu's strategy, and the relationship between history, function, and presentation form reveals that the main domain of Krumpyung Serambu and its existence still survive and strive for development, especially in the digitalization era.